On a genaralized uniform zero-two law for positive contractions of non-commutative L1-spaces - Ganiev, Inomjon; Mukhamedov, Farrukh; Bekbaev, Dilmurad (Institute of Physics Publishing, 2016)
In this paper we prove a non-commutative version of the uniform "zero-two" law for positive contractions of L1-spaces associated with von Neumann algebras.